Mode II brittle fracture: recent developments - A. Campagnolo; S.M.J. Razavi; M. Peron; J. Torgersen; F. Berto (Fracture and Structural Integrity)
Fracture behaviour of V-notched specimens is assessed using two energy based criteria namely the averaged strain energy density (SED) and Finite Fracture Mechanics (FFM). Two different formulations of FFM criterion are considered for fracture analysis. A new formulation for calculation of the control radius Rc under pure Mode II loading is presented and used for prediction of fracture behaviour. The critical Notch Stress Intensity Factor (NSIF) at failure under Mode II loading condition can be expressed as a function of notch opening angle. Different formulations of NSIFs are derived using the three criteria and the results are compared in the case of sharp V-notched brittle components under in-plane shear loading, in order to investigate the ability of each method for the fracture assessment. For this purpose, a bulk of experimental data taken from the literature is employed for the comparison among the mentioned criteria.